Socialization in health and fitness education: interpretation of notions, problems, perspectives. - Zavydivska N.N; Opolonets I.V (Kharkov National Pedagogical University, 2010)
This article embraces theoretical definition of the process of socialization. Socialization factors and their influence on the process of individual physical education have been considered and analyses. Their usages in the process of physical education with the help of which university students purposefully integrate into social and cultural environment have been substantiated. It is defined such factors of socialization as macrofactors, mezofactors and microfactors. It is well-proven that they are not equivalent on the possibilities and by meaningfulness, and also ability to influence on personality.